BASIC INFRASTRUCTURES AND THEIR DEVELOPMENT ISSUES OF TOURISM SECTOR IN TEHRAN PROVINCE (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
In the article the current situation and development issues of the tourism industry in the province of Tehran are given based on the analysis and generalization of factual material and statistical data of basic infrastructures, such as hotel service, air transport, vehicles, guides՛ institute and catering services.
Keywords: Tehran Province; tourism infrastructure; hotel services; transport services; food services; guides; development issues